2000
DOI: 10.1200/jco.2000.18.19.3325
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection Is Predictive of CNS Involvement in Systemic AIDS-Related Non-Hodgkin’s Lymphomas

Abstract: These results show that EBV infection of the tumor clone significantly increases the risk of CNS involvement by systemic AIDS-NHL, without regard of specific molecular features. The detection of EBV-DNA in the CSF of AIDS-NHL patients may select cases with higher risk of CNS involvement and, therefore, may prove useful in the therapeutic stratification of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 25 publications
0
35
1
Order By: Relevance
“…The incidence of CSF involvement at diagnosis ranges from 3% to 15%, and it is related to Burkitt's histology, extranodal involvement, and the use of highly active antiretroviral therapy (HAART). [20][21][22][23] Considering the high risk of progression during the treatment or recurrence during the remission, the use of intrathecal prophylaxis has been considered a mandatory part of the systemic treatment of HIV-NHLs. However, despite the use of standard treatment including methotrexate and/or cytarabine, the CNS recurrence remains a challenge in the outcome of these patients, with a recurrence rate of 4% to 5%.…”
mentioning
confidence: 99%
“…The incidence of CSF involvement at diagnosis ranges from 3% to 15%, and it is related to Burkitt's histology, extranodal involvement, and the use of highly active antiretroviral therapy (HAART). [20][21][22][23] Considering the high risk of progression during the treatment or recurrence during the remission, the use of intrathecal prophylaxis has been considered a mandatory part of the systemic treatment of HIV-NHLs. However, despite the use of standard treatment including methotrexate and/or cytarabine, the CNS recurrence remains a challenge in the outcome of these patients, with a recurrence rate of 4% to 5%.…”
mentioning
confidence: 99%
“…Although the diagnostic value of EBV-DNA for HIV-positive PCNSL is well-documented (3-10, 18), evidence showing its usefulness for identifying CNS lesions of systemic ARL is limited (3)(4)(5)(6)(7)(8)(9)(10). Since the prevalence (21.7%) of CNS involvement in patients with systemic ARL is considerably higher (3) than that of non-HIV lymphoma patients (2-7%) (14-16), our results might support the clinical utility of evaluating EBV-PCR with CSF in the management of patients with HIV-positive systemic ARL.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of AIDS-related lymphoma (ARL) has decreased following the advent of highly active antiretroviral therapy (HAART), the morbidity and mortality associated with this complication remain significant due to the aggressive clinical course and high frequency of extra nodal localization especially in the central nervous system (CNS) (1)(2)(3). Since the majority of patients with ARLs are diagnosed at the advanced stage of HIV infection, making the differential diagnosis of CNS lesions from other opportunistic diseases is crucial for the management of ARL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In a study of 50 patients with systemic ARL, Cingolani and colleagues 45 showed that presence of EBV infection in the primary tumor was an independent predictor for CNS lymphomatous involvement at diagnosis or eventual relapse. In addition, the authors also demonstrated that detection of EBV DNA in CSF by polymerase chain reaction could predict eventual CNS lymphomatous involvement in almost 100% of patients, 45 suggesting that the detection of EBV DNA in CSF may be used to select patients who would most benefit from CNS prophylaxis. Clinically, CNS chemoprophylaxis should be considered for patients with Burkitt lymphoma or with bone marrow, paraspinal, paranasal, epidural, testicular, or widespread systemic involvement.…”
Section: Role Of Central Nervous System Prophylaxismentioning
confidence: 99%